Factors Related to Behavior Handwashing Habits With Soap (CTPS) in Students of SD Negeri Kec. Alam Barajo Jambi City in 2024 - Bella Yumania Sari; Puspita Sari; Vinna Rahayu Ningsih (Formosa Journal of Multidisciplinary Research, 2024)
Washing your hands with soap is a very simple, easy action, and has great benefits in preventing various potentially fatal diseases. Based on Riskesdas data in 2018, the proportion of the population aged less than 10 years has increased from 47.0% in 2023 to 49.8% in 2018. According to Jambi city PHBS data in 2022, it is stated that the health center whose CTPS is classified as low is the Rawasari Health Center with a total of 42 schools but only 15 schools implementing CTPS, this research aims to analyze factors related to the habit of washing hands with soap (CTPS) among students at SD Negeri Alam Barajo District, Jambi City. This research uses a quantitative approach using a Cross-Sectional design. The number of samples used was 101 students who were selected using the Purposive Sampling technique. The research results showed that 60.4% of students had good CTPS behavior, 74.3% had good knowledge, 60.4% had a positive attitude, 53.5% had a teacher role, and 68.3% had complete facilities. Based on the results of statistical tests, the relationship between knowledge and the role of teachers with CTPS habitual behavior has a p-value of 0.305 and 0.718 (p > 0.05), while the relationship between attitudes and handwashing facilities and CTPS habitual behavior has a p-value of 0.000 and 0.035 (p < 0.05). Teacher knowledge and role do not have a significant relationship with CTPS habitual behavior, while attitudes and hand washing facilities have a significant relationship with CTPS habitual behavior. It is recommended to improve attitudes and hand washing facilities to improve CTPS behavior among students.